1997
DOI: 10.1017/s0033291797004856
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between mood and cognitive function studied with PET

Abstract: Background. Experimentally induced depressed mood is a suggested model for retarded depression. We describe the neural response associated with induced mood and the locus of the interaction between systems mediating mood and cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
1
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(115 citation statements)
references
References 62 publications
8
101
1
5
Order By: Relevance
“…These regions share extensive reciprocal connections with the amygdala, anterior temporal and anterior cingulate cortex (Ongur and Price, 2000). Functional neuroimaging studies in healthy subjects have demonstrated a role for the medial and lateral sectors of the IFC in mood regulation (Baker et al, 1997;Northoff et al, 2000) and in emotional memory (Cabeza and Nyberg, 2000). It has been speculated that the IFC is involved in the highest level of behavior regulation, including emotion regulation, through pathways between the IFC and autonomic systems that govern visceral responses associated with affective stimuli (Cabeza and Nyberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These regions share extensive reciprocal connections with the amygdala, anterior temporal and anterior cingulate cortex (Ongur and Price, 2000). Functional neuroimaging studies in healthy subjects have demonstrated a role for the medial and lateral sectors of the IFC in mood regulation (Baker et al, 1997;Northoff et al, 2000) and in emotional memory (Cabeza and Nyberg, 2000). It has been speculated that the IFC is involved in the highest level of behavior regulation, including emotion regulation, through pathways between the IFC and autonomic systems that govern visceral responses associated with affective stimuli (Cabeza and Nyberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic activity (serotonin transporters) peaks at 4 h after the injection 24,25 correspondingly. Since previous studies have not revealed significant changes in blood flow either in the hypothalamus/midbrain area or in the thalamus in depressive states 52 ]␤-CIT in prefrontal cortex is low and rather within PET than SPET resolution. 53 The equilibrium state of dopamine transporters in the striatum is reached 16-20 h after the injection.…”
Section: Molecular Psychiatrymentioning
confidence: 94%
“…Functional imaging experiments show aberrant perfusion and metabolism in this region of both disorders (Baker et al, 1997;Erkwoh et al, 1997;Haznedar et al, 1997;Rubinsztein et al, 2001), while magnetic resonance studies demonstrate decreased gray matter volume in patients with bipolar disorder (Drevets et al, 1997;Lopez-Larson et al, 2002). At the histopathological level, a reduction in laminar thickness and neuron densities in layers III, V, and VI of ACCx (Bouras et al, 2001) as well as decreases in glial cell density have been reported in ACCx of bipolars (Knable, 1999;Ongur et al, 1998).…”
Section: Introductionmentioning
confidence: 98%